Learning where the jobs are [career growth]. - Selinger, C. (IEEE spectrum)
This paper identifies several emerging technologies that promise career growth. These include digital rights management, display technologies, fingerprinting, organic electronics, alternative fuels and the hydrogen economy, and Wi-Fi. The paper also provides some useful tips on how to stay current on the latest industry developments and effectively manage a career in a fast-changing technology world.